2020
DOI: 10.22146/ijeis.35983
|View full text |Cite
|
Sign up to set email alerts
|

Penggunaan Deteksi Gerak untuk Pengurangan Ukuran Data Rekaman Video Kamera CCTV

Abstract: Some cases the recording data of Closed Circuit Television (CCTV) is stored for future use. In the long term usage, the files size will grow larger and requiring large storage devices. In some cases, the recorded data not only image with the desired object but also the background images that may be recorded for long periods of time. This cases make data storage device usage to be less effective. So this research will design a system of CCTV devices that capable to select images to reduce the size of stored ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…In this experiment, CCTV can be a tracking tool and detect the number of people. In addition, Sagala et al (2020) research uses motion detection to reduce CCTV recording data size. Their research found that the object detection system in visual data can detect objects with a precision level of 79.87% with a fast image processing speed with an average of about 38.67 images per second.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, CCTV can be a tracking tool and detect the number of people. In addition, Sagala et al (2020) research uses motion detection to reduce CCTV recording data size. Their research found that the object detection system in visual data can detect objects with a precision level of 79.87% with a fast image processing speed with an average of about 38.67 images per second.…”
Section: Discussionmentioning
confidence: 99%
“…CCTV dapat dipasang berbagai tempat dan sudut sesuai kebutuhan (Yusro & Diamah, 2022;Karinda et al, 2021). Tujuan pemasangan CCTV adalah untuk keamanan bersama terutama di lingkungan warga (Ramdhani et al, 2022;Fakhruddin et al, 2022) karena dapat menangkap gambar maupun rekaman secara real time (Sagala et al, 2020;Putriyanto et al, 2023;Junita & Fahmi, 2022;Susilo et al, 2023).…”
Section: Pendahuluanunclassified
“…Research on compression to reduce data volume has been conducted by developing motion detection recording modes [20]. In [21], other providing motion detection information, the CCTV video processing also provides two other output that is face detection information and identification information.…”
Section: Related Workmentioning
confidence: 99%